Pengembangan E-Modul IPAS Berbasis STEM Materi Tumbuhan dan Fungsinya Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Kelas IV Sekolah Dasar - Ferida Putri Tri Trisnani (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aimed to develop a STEM-based IPAS E-Module on the topic of plants and their functions to improve the critical thinking skills of fourth-grade elementary scool students. The research was motivated by the low level of students critical thinking skills, especially in analyzing, evaluating and creating, as well as the limited use of integrated digital teaching materials in clasroom learning. This study employed a Research and Development (R&D) method using the ADDIE model. The research subjects were fourth-grade students of SDN TegalGede 03 in the 2025/2026 academic year. The instruments used were expert validation sheets, student response quetionnaires and pre-test and post-test quetions. The efffectiviness of the product was analyzed using the N-Gain formula. The results showed that the developed E-Module met the criteria of validity in terms of content, language and design. It was categorized as pratical based on positive student responses and ease of use. The effectiviness test indicated a moderate improvement in students critical thingking skills. Therefore, the STEM-based IPAS E-Module is valid, practical and effective to support critical thinking development in elementary school learning
Validasi dan Finalisasi Ratna 15 Juli 2026
Keywords: E-Module; STEM; IPAS; Critical Thinking Skills